Digital Transformation and Supply Chain Resilience through Cloud, ERP, and BI Integration in Mondelez International - Azzaria, Ainu; v, Demitri Fernando Putra; Wicaksono, Soetam Rizky (Universitas Negeri Surabaya, 2026)
This study examines Mondelez International's digital transformation specifically its infrastructure migration to the cloud (AWS), SAP RISE ERP implementation, and Business Intelligence (Tableau) platform utilization with a focus on implications for procurement and supply chain resilience. The research method used was a Research & Development (R&D) approach based on a secondary literature review, followed by a SWOT analysis to evaluate internal and external factors, and a PEST analysis to examine the macro-environmental context. The results indicate that the integration of cloud + ERP + BI strengthens cross-functional data visibility, accelerates decision-making, and improves procurement efficiency but challenges remain from commodity dependence (cocoa), cross-border operational complexity, and fiscal/environmental regulations in certain jurisdictions. The study also identifies strategic opportunities for expansion into digital channels and new products, as well as the need for continued investment in factory automation to reduce costs. Proposed managerial implications include strengthening raw material hedging practices, accelerating factory digitalization, and sharpening product portfolio strategies to align with regulatory pressures and consumer preferences. These findings provide lessons for global FMCG companies in integrating technology, data, and operational strategies to enhance supply chain resilience. Keywords: Mondelez, digital transformation, SAP RISE, Tableau, supply chain resilience.